Mainstreaming Ecotheology: Empowering Women Activists in Jambi City - Junita Br Surbakti; Lahmuddin Lahmuddin; Fridiyanto Fridiyanto; Arfan Arfan; Annisa Berliana Difa; Nova Juwita (Abdimas Galuh, 2026)
Environmental degradation in Jambi City such as the pollution of the Batanghari River, increasing floods, and the decline of green open spaces demonstrates the urgent need to strengthen environmental conservation movements based on religious values. In this context, women activists occupy a strategic position as agents of change due to their close connection with community social dynamics. This community service program focuses on strengthening the capacity of women activists in mainstreaming ecotheology, utilizing local assets as internal community strengths, and developing cross-sector collaborative networks. The objectives include enhancing conceptual and practical competencies, optimizing local assets for ecological movements grounded in religious values, and expanding support through multisector partnerships. The program’s implementation shows that capacity building for women is a key factor in developing ecological awareness and encouraging environmental preservation at the community level. Conceptual and practical training strengthened skills in advocacy, leadership, and program management, enabling women to act as strategic drivers of change. The Asset-Based Community Development (ABCD) approach ensures program sustainability by utilizing individual, social, cultural, and physical community resources. Networking with government, religious institutions, educational organizations, media, environmental communities, and the business sector reinforced movement consolidation and opened broader collaboration. These efforts have the potential to foster an inclusive, participatory, and sustainable ecotheology movement.